2020
DOI: 10.3390/molecules25184079
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Oxidation Stability of Soybean Germ Phytosterols in Different Lipid Matrixes

Abstract: The stability of soybean germ phytosterols (SGPs) in different lipid matrixes, including soybean germ oil, olive oil, and lard, was studied at 120, 150, and 180 °C. Results on the loss rate demonstrated that SGPs were most stable in olive oil, followed by soybean germ oil, and lard in a decreasing order. It is most likely that unsaturated fatty acids could oxidize first, compete with consumption of oxygen, and then spare phytosterols from oxidation. The oxidation products of SGPS in non-oil and oil systems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
2
4
0
Order By: Relevance
“…This effect can be attributed to the thermal degradation caused by heating during the pre-treatment. It is known that phytosterols undergo oxidation when subjected to heating, as reported by Chen et al (2020) who studied the thermo-oxidative stability of soy germ phytosterols and reported that heating the oil to 120 °C for 60 min promoted a loss of ~8% in these phytosterols, which is in accordance with this study. However, α-tocopherol was not influenced by seed pre-treatment.…”
Section: Oil Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…This effect can be attributed to the thermal degradation caused by heating during the pre-treatment. It is known that phytosterols undergo oxidation when subjected to heating, as reported by Chen et al (2020) who studied the thermo-oxidative stability of soy germ phytosterols and reported that heating the oil to 120 °C for 60 min promoted a loss of ~8% in these phytosterols, which is in accordance with this study. However, α-tocopherol was not influenced by seed pre-treatment.…”
Section: Oil Characterizationsupporting
confidence: 91%
“…The consumption of vegetable oil with high quantities of linoleic and oleic acids can help to decrease low-density lipoproteins (LDL cholesterol), and consequently reduce the risk of heart disease (Sánchez-Muniz et al, 2016). The oil extracted from sunflower seeds is also composed of natural antioxidants, such as a-tocopherols, phytosterols, vitamins A, D and E, which aid in oxidative stability (Aquino et al, 2019;Chen et al, 2020), These components are in minor quantity and provide additional nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…Also has been demonstrated in rapeseed oil that sterol contents lower as the level of processing increases (crude, refining, and partial hydrogenation). Additionally, it was demonstrated that increments in heating time and temperature increased the loss rate of soybean germ phytosterols in different lipid matrix, including soybean germ oil, olive oil, and lard matrix [30]. Although those reductions were found in simulations without foods, using longer times than those used in our study, they already corresponded with the tendencies measured in AVO by us.…”
Section: Total and Individual Sterol Stanol Contentssupporting
confidence: 56%
“…Polyphenolic compounds in sunflower, soybean, canola and olive oils are better preserved during low-fat frying with microwave grilling and oven than deep-frying [27]; a net decrease of polyphenol species was measured in extra virgin olive oil after boil, boil in a water-oil mixture, deep fry, and sauté, of tomatoes, eggplant, potato and pumpkin [28,29]. The effect in sterol content of oil has been studied in long term treatments at high temperatures; after prolonged heating (48 h, 170 • C) of rapeseed oil was measured a steady decrease in sterol content ranging from 21% to 46% depending on the kind of oil analyzed (virgin or refined) [19]; it was also found in soybean, and in olive oil heated during 30 to 120 min, the reduction was more intense at 180 • C than at 120 to 150 • C [30]. Repeated frying sessions reduce sterol content in sunflower, palm oil, cottonseed oil, and virgin olive oil [7].…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase was observed in sterol oxidation products at each temperature and the concentration of sterol oxidation products increased with the temperature increase (Lin et al, 2017). The increase in sterol oxidation products and sterol loss by the thermal treatments above 100 °C was reported from different studies (Barriuso et al, 2015;Chen et al, 2020;González-Larena et al, 2011;Kemmo et al, 2008). It was reported that sterol oxidation products had cytotoxic effects and the rate of their formation increased by thermal treatment (Lin et al, 2017;O'Callaghan et al, 2014).…”
Section: Sterol and Fatty Acid Compositionsmentioning
confidence: 91%